1942
DOI: 10.1172/jci101281
|View full text |Cite
|
Sign up to set email alerts
|

The Prevention of Sensory Neuron Degeneration in the Pig, With Special Reference to the Rôle of Various Liver Fractions 1

Abstract: In previous reports (1, 2) a description was given of abnormal gait and degeneration in the nervous system which developed in pigs under certain experimental conditions. It was suggested that these effects were the result of a dietary deficiency and evidence was presented which indicated that the changes took place in spite of adequate amounts of vitamin A, thiamin, riboflavin, nicotinic acid or vitamin E. Inanition or mineral deficiency did not seem to play any role. It was shown that a nerve-protecting facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1942
1942
2001
2001

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Of interest is the study of vitamin B 6 deficiency that lasted the longest time, as long as 20 weeks, in pigs. 17 That study observed abnormalities in gait and "early degen- In the current study, the walking-track abnormalities began to be apparent at 4 months. Demonstration that the vitamin B 6 -deficient diet in fact produced a nutritional deficiency state was provided by quantitation of pyridoxol, pyridoxal, pyridoxal phosphate, and pyridoxic acid in the rat serum.…”
Section: Annals Of Plastic Surgerysupporting
confidence: 49%
See 1 more Smart Citation
“…Of interest is the study of vitamin B 6 deficiency that lasted the longest time, as long as 20 weeks, in pigs. 17 That study observed abnormalities in gait and "early degen- In the current study, the walking-track abnormalities began to be apparent at 4 months. Demonstration that the vitamin B 6 -deficient diet in fact produced a nutritional deficiency state was provided by quantitation of pyridoxol, pyridoxal, pyridoxal phosphate, and pyridoxic acid in the rat serum.…”
Section: Annals Of Plastic Surgerysupporting
confidence: 49%
“…Pyridoxine deficiency causes arteriosclerosis, fatty liver, and convulsions in monkeys 8 ; weakness, growth retardation, and convulsions in chickens 9 ; and neutropenia, 10 xanthuria, convulsions, 11,12 and seborrheic dermatitis 13,14 in humans, but has not been observed to have any effect on reproduction 15 or taste sensitivity 16 in the rat. The only neurological observations have been abnormal gait in pigs 17 and "sensory neuritis" in 3 of 50 people 14 in a short-term study of B 6 dietary deficiency.…”
mentioning
confidence: 99%
“…Convulsions and ataxia appear in pigs deficient in vitamin B, (Wintrobe, Mushatt, Miller, Kolb, Stein & Lisco, 1942; Follis & Wintrobe, 1945). There is demyelination of the sciatic and brachial nerves which is later found also in dorsal root fibres and the dorsal columns of the spinal cord.…”
Section: The Role Of Vitamins In Metabolic Processesmentioning
confidence: 99%